Effect of educational programme on patients with bronchial asthma regarding self -care management - Eman Talaat Elshmaa; Fatma Mostafa Mahrous; Shimaa Nabil Abdelsalam; Mayada Omar Elsadee (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the effect of educational programmes on patients with bronchial asthma regarding self-care management. Method: The quasi-experimental study was conducted at the El-Fayoum University Hospital, Egypt, from August 2021 to January 2022, and comprised patients of either gender aged >20 years who had a history of asthma attacks in the preceding 6 months. Data were collected through three questionnaires adapted from the literature regarding patients’ sociodemographic and clinical characteristics, their knowledge regarding asthma and self-care management, and their practices as noted through an observational checklist. After evaluation as a baseline, the subjects were given training through 30-minute sessions twice a week for a total of 10 sessions. They were also provided with a self-care management booklet in the Arabic language. The post-intervention evaluation was at the end of the 10-session programme and then again 3 months after the first evaluation. The collected data were statistically analyzed using the statistical package for social science (SPSS) version (20), percentage (%), the arithmetic mean (), standard deviation (SD), and chi-square (X2 & p-value). Results: Of the 100 patients with a mean age of 31.5±7.41 years, 34(34%) were in the 30-40 years bracket, 63(63%) were males, 70(70%) could read and write, 94(94%) lived in urban areas, 50(50%) were smokers and 81(81%) said asthma attack was triggered by consumption of certain foods. At baseline, 69(69%) patients had unsatisfactory knowledge and 72(72%) had unsatisfactory practices regarding self-care management. Post-intervention, there was a highly significant improvement in knowledge and practice scores (p=0.001). Conclusion: The educational intervention improved patients’ knowledge, practice, and self-care management. Keywords: Asthma, Mortality, Ambulatory care, Self-care management.